Chemical peels in melasma: A review with consensus recommendations by Indian pigmentary expert group - Rashmi Sarkar; Shehnaz Arsiwala; Neha Dubey; Sidharth Sonthalia; Anupam Das; Latika Arya; Narendra Gokhale; R G Torsekar; V K Somani; Imran Majid; Kiran Godse; G Ravichandran; et al. (Wolters Kluwer Medknow Publications, 2017)
Melasma is a notorious dermatosis, often resistant to treatment. Chemical peeling constitutes an acceptable option of management of melasma (of any type and duration). In this article, as a group of experts from Pigmentary Disorders Society (PDS) in collaboration with South Asian Pigmentary Forum (SPF), we have tried to elaborate the various chemical peeling agents for the treatment of melasma. Besides, we have reviewed the indications, mechanism of action, rationality and the detailed procedure of peeling. The evidence in favor of various peeling agents have been summarized as well.